Study of structural and electronic properties of graphene and some graphene derivatives based on orthorhombic unit cell by density functional theory - Thi Thoa, Tran; Chi Tuan, Vu; Tho Hoan, Pham; Van Hung, Hoang; Hue, Nguyen Thi Minh (Vietnam Journal of Science and Technology, 2022)
Pristine graphene and graphene derivatives have been investigated with the density functional theory (DFT). The calculations consist of structural optimization, density of states (DOS), projected density of states (PDOS) based on orthorhombic 4-atom unit cell. The obtained results are in good agreement with the experimental data. The highest deviations from the experiment are 0.35 % and 0.28 % for the lattice constant and bond length, respectively. In addition, the results of DOS, and PDOS have shed light on electronic properties of graphene. The functionalization of graphene leads to distortion of graphene sheet. New states around the Fermi level of graphene derivatives are mainly composed of 2p orbitals of carbon and oxygen atoms. Besides, structural and electronic properties of graphene and derivatives obtained from the 4-atom orthorhombic unit cell are in line with those from the traditional hexagonal 2-atom unit cell in the previous works. This result proved the reliability of the constructed orthorhombic 4-atom unit cell of graphene.